Metabolism of triflumuron in the human liver: Contribution of cytochrome P450 isoforms and esterases. (15th September 2019) - Timoumi, Rim; Buratti, Franca M.; Abid-Essefi, Salwa; Dorne, Jean-Lou C.M.; Testai, Emanuela
Highlights: In vitro phase I TFM metabolism was characterised in human samples for the 1 st time. Human recombinant CYPs 3A4 and 2C family are the most active isoforms at low TFM. At high TFM concentration CYP1A2 accounted for 1/3 of the hepatic phase I metabolism. The same CYPs are active in HLMs, with a 10-fold lower catalytic efficiency. Esterase in HLMs are more efficient than CYPs in TFM metabolism. Abstract: Triflumuron (TFM) is a benzoylurea insecticide commonly used in Tunisian agriculture and around the world to control crop pests and flies as a promising alternative to conventional insecticides for its arthropod specificity and low toxicity. From the evidence available in animal models, it can be expected that the metabolism of TFM is catalyzed by cytochrome P450 (CYP) and esterases. However, no data are available on human metabolism of TFM with regards to phase I metabolism and CYP isoform specificity. Hence, this manuscript describes experimental investigations to underpin in vitro phase I TFM metabolism in human samples for the first time. TFM biotransformation by recombinant human CYPs was characterized, then human liver microsomes (HLM) and chemical specific inhibitors have been used to identify the relative contribution of CYPs and esterases. Our results showed that all CYP isoforms were able to metabolize TFM with different affinity and efficiency. The relative contribution based both on the kinetic parameters and the CYP hepatic content was 3A4 > >2C9 > 2C8 > 2A6 > 1A2 > 2B6 > 2D6 > 2C19 > 2C18 > 1A1 at low TFM concentration, whilst at high TFM concentration it was 1A2 > >2C9 = 3A4 = 2A6 > 2C19 > 2B6 = 2C8 > 2D6 > 1A1 > 2C18. Experiments with HLMs confirmed the involvement of the most relevant CYPs in the presence of specific chemical inhibitors with a catalytic efficiency (Cli app ) lower by an order of magnitude compared with recombinant enzymes. Esterases were also relevant to the overall TFM kinetics and metabolism, with catalytic efficiency higher than that of CYPs. It is foreseen that such isoform-specific information in humans will further support in silico models for the refinement of the human risk assessment of single pesticides or mixtures.